The Use of the E-Library in Umaru Musa Yar’adua University Library - Adewole , Segun; Batagarawa, Saddiq A. (MiddleBelt Journal of Library and Information Science, 2013)
This study was motivated by the high level of investment and commitment being made by the authorities of the Umaru Musa Yar’Adua University (UMYU) and the Library on the provision and development of electronic services to its users. There is the concern to see the justification of this provision through the analyses of the use by the users’ community. The vision of the founders of the Library is to run a near perfect electronic Library environment. Data were collected through a structured eight items, 34-question questionnaire, administered on the first 100 users of the e-Library facility of the Library; on the basis of “Administration while stock last”. The completed copies of the questionnaire were collected upon completion, on an on-the-spot basis, resulting in a 100% return/response rate. More than 70% of the users are male and 87% are single; 97% are students of the University; with students from the Department of Education being the highest users; 75% and 55% using this facility to do assignments and for research purpose respectively, while Google and Yahoo are the two most used search engines.. Also, 98% of the users are computers literate; but only 42% are very good on the machine, while the remaining 56% are fairly computer literate. Among others, the study recommended that a course on ”Use of Computer” be made compulsory for all students of the University so as to achieve a 100% ICT compliant university environment and attain the goal of the Library.